Highly brain-permeable apoferritin nanocage with high dysprosium loading capacity as a new T2 contrast agent for ultra-high field magnetic resonance imaging. (June 2020) - Kim, Hee-Kyung; Baek, Ah Rum; Choi, Garam; Lee, Jung-jin; Yang, Ji-ung; Jung, Hoesu; Lee, Taekwan; Kim, Dongkyu; Kim, Minsup; Cho, ArtE.; Lee, Gang Ho; Chang, Yongmin
Abstract: High sensitivity at ultra-high field (UHF) and sufficient potential to penetrate the brain are the most desirable characteristics in the development of contrast agents (CAs) for magnetic resonance imaging (MRI). However, incorporating such qualities into a single nanocarrier is challenging. Herein, we report a new strategy for a highly brain-permeable MR CA with high sensitivity at UHF by loading dysprosium chelates (DyL) in apoferritin cavities (Apo-DyL). We also design the chelate ligand structure to increase DyL loading capacity within the apoferritin cavity. Using the intracerebroventricular (ICV) injection approach as a new delivery route for Apo-DyL, we demonstrate that apoferritin loaded with DyL can penetrate the brain–ventricular barrier and diffuse into the brain. This brain-permeable capability is unique to Apo-DyL, compared with other types of nanoparticles used in MRI. Apo-DyL also shows significant increase in MR sensitivity of DyL at UHF. Furthermore, based on brain tumor imaging at UHF, Apo-DyL can significantly enhance the tumor for a lower dose of the CA than the previously reported Gd- or Mn-loaded apoferritin nanoplatform. Therefore, Apo-DyL can be a novel nanoplatform that is a highly sensitive and versatile MR CA for UHF brain imaging.